Structural competency curriculum in health sciences education: a scoping review. - Gholar, Victoria M.; Palokas, Michelle; Tacy, Joseph (JBI Evidence Synthesis, 2023)
Objective: The objective of this review was to explore what is known about implementing and evaluating the structural competency framework in undergraduate and graduate health science programs. This review also sought to identify outcomes that were reported as a result of adding this training to various curricula. Introduction: The structural competency framework was introduced in 2014 to train pre-health and health professionals to understand broader structures that influence health inequities and outcomes of health. Across the globe, programs are incorporating structural competency in the curricula to address structural issues that impact interactions in the clinical setting. The implementation and evaluation of structural competency training across multiple health science programs are poorly understood and deserve further examination. Inclusion criteria: This scoping review considered papers that described the implementation, evaluation, and outcomes of structural competency training for undergraduate or graduate students and postgraduate trainees in health science programs in any geographic location. Methods: Papers published in English that addressed the implementation and evaluation of structural competency frameworks in undergraduate and graduate health science programs were included. No date restrictions were imposed. The databases searched included MEDLINE (PubMed), CINAHL (EBSCO), Scopus, Embase, EuropePubMed Central (European Bioinformation Institute), PsycINFO (EBSCO), and Education Resources Information Center (ERIC). Sources of unpublished studies and gray literature searched included ProQuest Dissertations and Theses (ProQuest), PapersFirst (WorldCat), and OpenGrey. Screening of full-text papers and data extraction were performed independently by 2 reviewers. Results: Thirty-four papers were included in this review. Implementation of structural competency training was described in 33 papers, evaluation of training was described in 30 papers, and outcomes were reported in 30 papers. Throughout the included papers, the methods/pedagogical approaches to implementing structural competency in curricula varied. Evaluations focused on knowledge, skills, abilities, attitudes of students, quality, perceptions, and effectiveness of training. Conclusions: This review revealed that health educators have successfully implemented structural competency training in medical, pharmacy, nursing, residency, social work, and pre-health programs. There are multiple methods of teaching structural competency, and trainers can adapt delivery methods for different educational contexts. Neighborhood exploration; photovoice, including community-based organizations in clinical rotations; incorporating team-building exercises; case-based scenarios; and peer-teaching are among the innovative approaches that can be used to deliver the training. Training can be provided in short intervals or incorporated throughout an entire study plan to enhance students' structural competency skills. Methods of evaluating structural competency training vary and include qualitative, quantitative, and mixed methods.